Análise de bulhas cardíacas usando wavelets visando auxiliar no diagnóstico médico - Brites, Ivo Sérgio Guimarães [UNESP] (2014)
This dissertation aims to present a proposal for interpretation of heart sounds using Discrete Wavelet Transform. The heart sounds recorded in a digital file were processed using level 6 of db7 and level 6 of db6 Daubechies Discrete Wavelet Transform and extracting the media and standard deviation features. The standard deviation of level6 of db6 Daubechies Discrete Wavelet is are able to differentiate between normal and abnormal from database of 70 heart sound signals with 95.71% of correct classifications